The Effect of Sugar Variation and Fermentation Time on Hydrogen Peroxide Levels and Eco-Enzyme Antibacterial Activity - Primarista, Ni Putu Vidya; Wali, Abdul Rohman; Syahwardini, Trisuciati (Jurnal Biologi Tropis, 2026)
Eco-enzyme is a filtrate resulting from the fermentation of sugar, organic materials, and water, which is produced not only to reduce organic waste but also as a functional product. This study aims to examine the effects of sugar type and the eco-enzyme's fermentation duration on three key parameters: bacterial optical density, hydrogen peroxide concentration, and inhibition zone against Staphylococcus aureus and Escherichia coli. The bacterial optical density was determined from absorbance measured at 600 nm using a UV-Vis spectrophotometer, the hydrogen peroxide concentration was determined by permanganometric titration, and the inhibition zone of the eco-enzyme against Staphylococcus aureus and Escherichia coli was determined using the disc diffusion method. The results showed that the eco-enzyme fermented with molasses for one month had the highest bacterial optical density. Meanwhile, the highest hydrogen peroxide concentration was found in the eco-enzyme fermented with molasses for three months. In addition, the eco-enzyme fermented with molasses for three months exhibited the highest antibacterial activity against Staphylococcus aureus and Escherichia coli, with inhibition zones of 6.59 mm and 6.37 mm, respectively. Eco-enzymes fermented with granulated sugar, palm sugar, and molasses all showed antibacterial activity against Staphylococcus aureus and Escherichia coli. However, the highest antibacterial activity against both bacteria was observed in the eco-enzyme fermented with molasses for three months.